Exosomes Isolated From Platelet-Rich Plasma and Mesenchymal Stem Cells Promote Recovery of Function After Muscle Injury. Issue 9 (July 2020) - Iyer, Shama R.; Scheiber, Amanda L.; Yarowsky, Paul; Henn, R. Frank; Otsuru, Satoru; Lovering, Richard M.
Background: Clinical use of platelet-rich plasma (PRP) and mesenchymal stem cells (MSCs) has gained momentum as treatment for muscle injuries. Exosomes, or small cell–derived vesicles, could be helpful if they could deliver the same or better physiological effect without cell transplantation into the muscle. Hypothesis: Local delivery of exosomes derived from PRP (PRP-exos) or MSCs (MSC-exos) to injured muscles hastens recovery of contractile function. Study Design: Controlled laboratory study. Methods: In a rat model, platelets were isolated from blood, and MSCs were isolated from bone marrow and expanded in culture; exosomes from both were isolated through ultracentrifugation. The tibialis anterior muscles were injured in vivo using maximal lengthening contractions. Muscles were injected with PRP-exos or MSC-exos (immediately after injury and 5 and 10 days after injury); controls received an equal volume of saline. Histological and biochemical analysis was performed on tissues for all groups. Results: Injury resulted in a significant loss of maximal isometric torque (66% ± 3%) that gradually recovered over 2 weeks. Both PRP-exos and MSC-exos accelerated recovery, with similar faster recovery of contractile function over the saline-treated group at 5, 10, and 15 days after injury ( P < .001). A significant increase in centrally nucleated fibers was seen with both types of exosome groups by day 15 ( P < .01). Genes involved in skeletal muscle regeneration were modulated by different exosomes. Muscles treated with PRP-exos had increased expression of Myogenin gene ( P < .05), whereas muscles treated with MSC-exos had reduced expression of TGF-β ( P < .05) at 10 days after muscle injury. Conclusion: Exosomes derived from PRP or MSCs can facilitate recovery after a muscle strain injury in a small-animal model likely because of factors that can modulate inflammation, fibrosis, and myogenesis. Clinical Relevance: Given their small size, low immunogenicity, and ease with which they can be obtained, exosomes could represent a novel therapy for many orthopaedic ailments.